P-24 DESCRIPTION OF SERUM MICRORNAS EXPRESSION AMONG INDIVIDUALS WITH VIRAL HEPATITIS AND LONG COVID - Lucas da Silva Lima; Juliana Maul Cardoso; Iolanda Raquel Paulo Ferreira; Luciane Leon Almeida Amado; Otacilio Moreira Da Cruz; Wagner Luis Coelho da Costa Nunes Pimentel; Lia Lewis Laura; Vanessa Salete De Paula; Giovana Angelice Paula; Livia Villar Melo (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Long COVID syndrome affects millions of people and is characterized by the permanence of signs and symptoms after 90 days of SARS-CoV-2 infection. MicroRNAs (miRNAs) are small non-coding RNAs that are related to different conditions and can characterize profiles including liver disease. OBJECTIVES: Characterize the serum expression of miRNAs in relation to viral hepatitis B and C and Long COVID. Patients / Materials and Methods: Serums were obtained from 69 individuals from 4 groups: (i) only Long COVID (n=18); (ii) Viral Hepatitis/Long COVID (n=21); (iii) only Viral Hepatitis (n=10) and (iv) control individuals (n=20). MiRNAs were isolated using a commercial extraction kit and miR-122, miR-143 and miR-223 were evaluated using quantitative real-time PCR. The expression of the examined genes was calculated from the formula RQ = 2-ΔΔCT. Statistical analysis was carried out using GraphPad Prism 9.5.1 software. Results and Discussion: The upregulation of the miRNAs analyzed was observed in the groups with diseases compared to the control, all with statistical significance (p<0.05). Of the groups with diseases, the Viral Hepatitis/Long COVID group showed the highest expression of all three miRNAs analyzed. For miR-122, the Viral Hepatitis/Long COVID and only Viral Hepatitis groups were up-regulated with mean RQ of 100.38 ± 122.06 and 80.72 ± 173.16, respectively, compared to the control 3.20 ± 8.75 (p<0.05). For miR-143 and mir-223, the highest expression was in the Hepatitis/Long COVID (mean RQ: 316.36 ± 572.96 and 270.45 ± 558.55, respectively) followed by the only Long COVID group (mean RQ: 158.12 ± 262.42 and 115.65 ± 191.30, respectively), both with statistical significance when compared to the control (mean RQ: 4.12 ± 5.37 and 3.78 ± 8.5, respectively). Conclusions: The presence of disease affects the expression of these miRNAs when compared to healthy individuals. The description of these targets will contribute to the understanding of Long COVID and its association with other diseases.